ADOPTION OF CULTIVATION TECHNOLOGIES AND FARMER GROUP DYNAMICS AS DETERMINANTS OF SARINAH RICE FARMING PERFORMANCE: A PATH-ANALYSIS APPROACH - Samantha, Yuliana; Dasipah, Euis; Permana, Nendah Siti; Sari, Devita Marwana; Nugraha, Elly Halimiyati (Agric, 2025)
Adoption of superior varieties is a strategy for maintaining regional food production. Sarinah rice cultivar is a type of rice that is resistant to several types of pests and plant diseases. This variety is cultivated by farmers in several areas in West Java Province. This study aims to investigate: (1) the association between rice cultivation technology and farming performance; (2) the relationship between farmer group dynamics and farm performance; and (3) the joint effects of rice cultivation technology and farmer group dynamics on the overall performance of rice farming. This study employed a survey method, with the analytical unit consisting of farmers who are members of farmer groups cultivating Sarinah rice cultivar in Bojongpicung Subdistrict, Cianjur Regency, West Java Province. Sampling technique was carried out using a census approach, involving a total of 30 respondents. Collected data were analysed using path analysis, with analytical procedures aligned with results of hypothesis testing. Results of study indicate that adoption of rice cultivation technology is significantly associated with farming success, accounting for 30.4% of variation. In comparison, farmer group dynamics show a stronger significant association, explaining 64.0% of the variation. Among two factors, farmer group dynamics exhibited strongest relationship with farming success. Rice cultivation technology and farmer group dynamics, when considered simultaneously, have a significant combined effect on farming success, accounting for 94.4% of the variation. Remaining 5.6% is attributed to other factors that were not examined in this study.